Deep learning in education: a bibliometric analysis - Wibawa, Aji Prasetya; Dwiyanto, Felix Andika; Utama , Agung Bella Putra (Bulletin of Social Informatics Theory and Application, 2022)
This study investigates the application and development of deep learning in educational settings. Based on the statistics of scientific papers, analysis done using bibliometrics demonstrates the rise of deep learning in educational settings. Deep learning is having a transformative effect on all aspects of education and learning, as well as research. These findings could pave the way for more investigation into deep learning, particularly in education. According to the bibliometric results, the Netherlands, China, the United States of America, India, and Norway are the five countries that have contributed the most to deep learning in education. Norway came in fifth place. In addition, some of the possible directions that research could go in the future concerning deep learning in education include online, machine, blended, remote, informal, and deep reinforcement learning.